Dinamika Gender dalam Pujian: Studi Sosiopragmatik Lintas Budaya pada Juri Ajang Pencarian Bakat dalam Bahasa Inggris dan Indonesia - Anindita, Maharani Laksmi (UIN Alauddin Makassar, 2025)
The use of a language is governed by several social factors that exist in its speech community. Gender is one of the factors where each gender could have different norms within their speech behavior, including in complimenting. This descriptive-comparative qualitative research aims to understand the strategies and functions of compliments based on gender in English and Indonesian in America's Got Talent and Indonesia's Got Talent 2023. The results of this study show that, regarding frequency, English female judges are more frequent in giving compliments, while in Indonesian, the gender distribution is more balanced. Both genders in both languages used direct and indirect compliment strategies. However, there is a difference in indirect compliment strategies, where in English, it is used evenly by both genders. In contrast, in Indonesia, women use indirect compliments in tiny numbers. Furthermore, the syntax structures and focus of direct compliments in English and Indonesian also exhibit differences. In English, both genders prefer personal pronouns, such as I, she, he, or they, in their compliment structure, though the male judges focused more on non-personal compliments, opposite to the female judges. In Indonesian, both genders avoid using personal pronouns and directly use noun phrases referring to their compliment's subject. Both genders also prefer to utilize a non-personal focus on their compliments. The function of compliments in both languages ​​shows more similarities and only differs in one function, namely, the function of refining the Face Threatening Act (FTA